DIAGNOSIS DAN TATALAKSANA OCHRONOSIS EKSOGEN - Stella Sunur; Yuli Kurniawati (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2023)
Exogenous ochronosis (EO) is a skin pigmentation disorder caused by the long-term use of topical skin lightening agents, especially hydroquinone. Cases of EO are rare. The etiopathogenesis of EO is still unknown. Clinical manifestations of EO are asymptomatic gray-brown or blue-black macules with a predilection for sun-exposed areas and no systemic involvement. The clinical manifestations of EO often resemble other dermal hyperpigmentation, so an adequate history and physical examination is necessary to avoid misdiagnosis. Histopathological examination is the gold standard for the diagnosis of EO. Management of EO is still a challenge in dermatology because EO is difficult to treat with variable and often unsatisfactory therapeutic results. Exogenous ochronosis management can be divided into non-pharmacological, pharmacological, laser and non-laser procedural, and combinations. Keywords: Exogenous ochronosis, EO, diagnosis, treatment